Intake of Lipid-based Nutrient Supplements during Illness and Convalescence among Moderately-underweight Malawian Childrenhomes - Flax, Valerie L (Journal of Health, Population and Nutrition, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi:10.3329/jhpn.v26i4.1891 J Health Popul Nutr 2008 Dec:26(4):468-470